Effects of non-homogeneity and oxide coating on silver nanowire networks under electrical stress: comparison between experiment and modeling. (10th August 2021) - Papanastasiou, Dorina T; Charvin, Nicolas; Resende, Joao; Nguyen, Viet Huong; Sekkat, Abderrahime; Muñoz-Rojas, David; Jiménez, Carmen; Flandin, Lionel; Bellet, Daniel
Abstract: Silver nanowire (AgNW) networks are among the most promising indium-free, flexible transparent electrodes for energy, lighting and heating devices. However, the lack of stability of such networks is a key factor that limits their industrial application. While applications require homogeneous networks, non-homogeneous AgNW networks are intentionally prepared in the present work to probe the mechanisms leading to failure under electrical stress. We show that induced non-homogeneities have a strong impact both on the spatial distribution of temperature (measured by IR imaging) and the current density throughout the electrode (as deduced from modeling). Regions with higher current density under elevated electrical stress are correlated to the origin of degradation. Furthermore, the influence of a zinc oxide (ZnO) layer on electrical performances of non-homogeneous specimens is studied. Thanks to ZnO coating, the tortuosity of electrical potential lines measured by the one-probe mapping technique is much lower than for bare networks. Additionally, coated network electrical failure occurs at 40% higher voltage compared to bare network, over 18 V, while reaching superior power-induced heating of 360 °C. The results presented here will contribute to the design and fabrication of more robust nanowire networks, particularly for application in transparent heaters.